Case Study of the Phenomenon of Educational Violence and Its Impact On the Psychology of Santri in Several Islamic Boarding Schools in Sukoharjo Central Java - Riyadi, Ahmad Ali; Khoiriyah, Khoiriyah; Zahra, Indi Aqilah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This article is field research that aims to reveal the phenomenon of violence in the world of education in Islamic boarding schools. This study is significant to carry out as input for knowledge in the world of education. Therefore, the research method used was interviews, observation and phenomenological analysis to uncover this case. The phenomenological analysis of this research study found violence in the Islamic boarding school environment. Violence has become mainstream in Islamic boarding school learning patterns. In general, the learning violence model occurs as a form of communication between caregivers and students or fellow students, which results in physical and psychological violence, physically in the form of violence that results in injuries such as being hit and abused. Psychological violence takes the form of emotional violence carried out utilizing bullying, sexual harassment, and violence under the pretext of disciplining students.